“Corporate Economy”. The Origins of Modern Neo-corporatism Practicein Western European Countries - Igor N. Shapkin (Мир новой экономики, 2018)
Object. Modern Western European society to a large extent develops on the basis of theoretical views and practice of corporatism. The study of the origins of the theory and experience of corporate construction is important for understanding the features of the modern stage and the future development of the region. Corporatism, the new “corporate economy” in the national economic science has not yet become the subject of independent research. The purpose of the study is to determine the factors that contributed to the development of corporatist concepts, developed in the “neo-corporatism” theory, in the analysis of the historical experience of the use of corporatist practices, in the consideration of manifestations of this concept in the current thought and activities of Western European countries. Methodology. The study is based on the dialectical approach using historical-genetic, system-structural and historical-typological methods. Results. Corporatism organically combined religious and secular views. In the 1920s-1930s, a number of European States set the goal of building a corporate state. During this period, corporatism was seen as an alternative to Soviet socialism and Western European liberalism. In the middle of the twentieth-century interest in corporatism revived, there is a new “neo-corporatist” theoretical and practical reality. As history shows, Western Europe, corporatism is never left out of the political and economic life. Summary. Modern corporatism is not interested in the ideas of social Christianity, it is not associated with the ideology of fascist “corporatism”. Today, as an instrument of reconciliation of different social interests, it is organically integrated into the system of public administration, thus allowing balanced socio-economic policy, to have a positive impact on economic growth, to ensure a stable level of employment and income distribution. But this social model has shortcomings. In particular, it is unable to respond quickly and adequately to the need for structural adjustment of the economy, to increase requirements for management and labor. Negative aspects are the decrease in flexibility and openness towards innovation and the opacity of decision-making.